KESIAPAN MEMBACA (READING READINES) PADA ANAK USIA TAMAN KANAK-KANAK - hartini, Sri (UNIVERSITAS SLAMET RIYADI, 2011)
ABSTRACTChildren are young who need many experiences form their enironment. It can be found throught their eyes, ears,mouth,nose or skin. Among those, eyes influence more than others on reading-readiness. Reading readiness is a foundamental for real reading and improve potential children at kindergarten School because by reading they can be learn everything. Three factors that influence reading-readiness are: family reading habit,fasilitation as home library, and social environment habit. Thos it can be concluded reading-readiness is very important to improve and develop the children at Kindergarten Scool.Â Keywords: reading-readiness, Children,Young learnes,and Kindergarten School.